Facile Synthesis of Ce–Doped SnO2 Nanoparticles: A Promising Photocatalyst for Hydrogen Evolution and Dyes Degradation. Issue 13 (2nd April 2019) - Kumar, Vinod; Bhawna,; Yadav, Sanjeev Kumar; Gupta, Akanksha; Dwivedi, Bhavna; Kumar, Anup; Singh, Prashant; Deori, Kalyanjyoti
Abstract: This report discussed the efficient hydrogen generation via water splitting and fast dye degradation pathway using Ce doped SnO2  nanoparticles. One pot synthesis of Ce doped SnO2  nanoparticles was carried out by a simple, convenient wet chemical method using H2 O2 and the product obtained was characterized using array of physico‐chemical techniques. Powder X‐ray diffraction confirmed the presence of rutile phase. Band gap for Ce:SnO2 was found out to be 3.80 eV which is more than the pure SnO2 (3.71 eV) and it is due to Moss‐Burstein effect. EDAX analysis and elemental mapping support uniform distribution of 5% Ce and the SEM imaging depicts irregular shape of nanocrystallites. The doping of 5% Ce into the interstitial and lattice positions of SnO2  nanoparticles was also confirmed by the X‐ray photoelectron spectroscopy analysis. Raman measurement and photoluminescence analysis showed the presence of oxygen vacancies and disorderness in the nanoparticles. Photocatalytic water splitting proficiency was investigated using Ce doped SnO2  nanomaterials in the presence of NiO as co‐catalyst and other different sacrificial reagents such as methanol, Na2 S‐Na2 SO3, EDTA ions, triethanolamine and in combinations. It was found that the evolution of H2  is maximum i. e. 25 μmol/g/h in presence of as‐synthesized catalyst, NiO (co‐catalyst) along with EDTA and methanol as scavengers under UV light irradiation. Further, the degradation of methylene blue and methyl orange dyes was investigated under UV‐Visible irradiation using Ce:SnO2 NPs. Abstract : The novelty of the work: One‐pot synthesis of Ce: SnO2 nanoparticles provides new prospects for energy and environmental related areas. XPS results confirmed the presence of 5% Ce 3+ /Ce 4+ ions and oxygen vacancies in the lattice. These oxygen vacancies together with co‐catalyst and scavengers played indispensable role in the generation of dihydrogen. Ce:SnO2 found to be potential photocatalyst for hydrogen generation through water splitting reaction and furthermore, it can effectively degrade dyes such as MB and MO.